First report of soft rot disease on pak choi (Brassica chinensis) caused by Dickeya dadantii subsp. dieffenbachiae in Malaysia - Golkhandan, Elham; Sijam, Kamaruzaman; Mior Ahmad, Zainal Abidin; Nasehi, Abbas (American Phytopathological Society, 2016)
In June 2012, a soft rot disease of pak choi (Brassica chinensis) was observed in the vegetable-growing region of Cameron Highlands, in the Pahang state of Malaysia. Disease symptoms first appeared as small, water-soaked lesions at the base of petioles. The lesions enlarged rapidly and spread to the leaves, resulting in the collapse of the plant. Diseased samples were randomly collected from 12 infested fields. Soft rot incidence on pak choi varied from 38 to 56% in different commercial fields. The causal pathogen was identified as Dickeya dadantii subsp. dieffenbachiae based on morphological, biochemical, genetic (RFLP) and pathogenicity analyses. This is thought to be the first report of soft rot on pak choi caused by D. dadantii subsp. dieffenbachiae in Malaysia.